The Triple Pillar Of MSMEs Development: Financial Literacy, Inclusion, And Financial Management - Indyah Herdiyanti; Sari Yuniarti; Gaguk Apriyanto (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2024)
This research aims to present empirical data demonstrating how financial management mediates the relationship between financial inclusion and financial literacy on the MSMEs' development. This particular type of research takes the form of explanatory research with the population of MSME actors in the environment-based tourism village of Sanankerto, Malang Regency. The study sample amounted to 125 taken through the purposive sampling method. Primary data from questionnaire findings given to respondents directly make up the utilized data. Data analysis in the form of PLS-SEM results indicates that financial management is positively impacted by financial literacy and financial inclusion and that these factors positively impact the MSMEs' development. It was also shown that financial management can mediate between financial inclusion and financial literacy in the MSME's development.